2021
DOI: 10.1080/20008198.2021.1877026
|View full text |Cite
|
Sign up to set email alerts
|

Do morally injurious experiences and index events negatively impact intensive PTSD treatment outcomes among combat veterans?

Abstract: Zalta (2021) Do morally injurious experiences and index events negatively impact intensive PTSD treatment outcomes among combat veterans?,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Additionally, if the provider reported an affirmative response of "Moderately Agree" to "Strongly Agree" on items 1-6 (i.e., perceived transgressions by self or others; e.g., "I saw things that were morally wrong," "I acted in ways that violated my own moral code or values," "I violated my morals by failing to do something I felt I should have done,") and items 7-9 (i.e., perceived betrayal by others; e.g., "I feel betrayed by leaders who I once trusted," "I feel betrayed by fellow medical providers who I once trusted,") then these specific PMIEs were coded as having occurred. This dichotomous scoring approach has been used in several prior investigations [17,18]. Additionally, the MIES has been found to have strong internal validity, temporal stability, and concurrent validity [2].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, if the provider reported an affirmative response of "Moderately Agree" to "Strongly Agree" on items 1-6 (i.e., perceived transgressions by self or others; e.g., "I saw things that were morally wrong," "I acted in ways that violated my own moral code or values," "I violated my morals by failing to do something I felt I should have done,") and items 7-9 (i.e., perceived betrayal by others; e.g., "I feel betrayed by leaders who I once trusted," "I feel betrayed by fellow medical providers who I once trusted,") then these specific PMIEs were coded as having occurred. This dichotomous scoring approach has been used in several prior investigations [17,18]. Additionally, the MIES has been found to have strong internal validity, temporal stability, and concurrent validity [2].…”
Section: Methodsmentioning
confidence: 99%
“…Two case studies found reductions in PTSD and depression symptoms for US veterans with MI-related injurious index traumas following standard PE and CPT (Held et al, 2018 ; Paul et al, 2014 ). One study assessed the effectiveness of an intensive outpatient PTSD program (massed-CPT), consisting of group CPT and individual CPT (in conjunction with mindfulness and yoga sessions) and found similar trajectories for PTSD and depression symptoms in veterans endorsing MI-related PTSD (e.g., history of MI; index trauma involved a PMIE) compared to those with PTSD without a PMIE exposure (Held et al, 2021 ). Another case study found reductions in PTSD but no change in depression symptoms, following massed-PE in US active-duty personnel with MI-related index traumas (Evans et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The instructions for the MIES were modified for the present study, and participants were instructed to answer the questionnaire and indicate how much they agreed/disagreed with items regarding their work as a VP. Previous studies have found the MIES to have good psychometric properties, with good internal consistency (Bryan et al, 2016 ; Held et al, 2021 ).…”
Section: Methodsmentioning
confidence: 94%